2017
DOI: 10.1002/ece3.2993
|View full text |Cite
|
Sign up to set email alerts
|

Population differences in host plant preference and the importance of yeast and plant substrate to volatile composition

Abstract: Divergent selection between environments can result in changes to the behavior of an organism. In many insects, volatile compounds are a primary means by which host plants are recognized and shifts in plant availability can result in changes to host preference. Both the plant substrate and microorganisms can influence this behavior, and host plant choice can have an impact on the performance of the organism. In Drosophila mojavensis, four geographically isolated populations each use different cacti as feeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…The necroses of each cactus differ in their chemical composition as well as the yeast and bacterial communities on which D. mojavensis feeds [ 56 – 58 ]. It has been shown that these populations not only differ in terms of their performance while utilizing different necrotic cacti [ 59 ], but also exhibit different behavioral and electrophysiological responses of olfactory organs, which suggests that their peripheral nervous system has been shaped by local ecological differences [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The necroses of each cactus differ in their chemical composition as well as the yeast and bacterial communities on which D. mojavensis feeds [ 56 – 58 ]. It has been shown that these populations not only differ in terms of their performance while utilizing different necrotic cacti [ 59 ], but also exhibit different behavioral and electrophysiological responses of olfactory organs, which suggests that their peripheral nervous system has been shaped by local ecological differences [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Saccharomyces are not only associated with fruit flies, but other insects including bees and wasps (Goddard et al 2010;Stefanini et al 2012). While specific flies prefer particular yeasts over others (Palanca et al 2013, Buser et al 2014, Scheidler et al 2015 and differ in their attraction to infested substrates (Matavelli et al 2015, Date et al 2017, only a few genera of yeasts are consistently associated with fruit fly populations. Frequently isolated yeasts include Candida, Pichia, Hanseniaspora, Metschnikowia, Torulaspora but rarely Saccharomyces (Hamby et al 2012, Stamps et al 2012, Buser et al 2014, Lam and Howell 2015.…”
Section: Are Yeast-fly Associations Just Chance?mentioning
confidence: 99%
“…Recent studies testing host plant specificity of cactophilic D. majovensis state that olfactory preference for the plant species can shift in response to plant-microbe and microbe-microbe interactions thus emphasising the importance of each partner to volatile composition in this three-way interaction (Date et al 2017). While yeasts might play a role in Drosophila phylogenetic diversification, there are no data to suggest that yeast speciation coevolved with Drosophila or flying insects in general, as yeasts evolved before flying insects emerged.…”
Section: Are Yeast-fly Associations Just Chance?mentioning
confidence: 99%
“…However, the impact of the fruit component on the putative yeast‐fly association has received little attention. Studies testing host plant specificity of cactophilic D. mojavensis show that host plant preference can shift in response to plant–microbe and also microbe–microbe interactions (Date, Crowley‐Gall, Diefendorf, & Rollmann, ). However, it is not known whether different fruit substrates alter the mode of any yeast‐fly interaction, and thus the degree to which the past and future evolution of yeast–fly interactions are affected by the plant host.…”
Section: Introductionmentioning
confidence: 99%